Case Note: The South China Sea Dispute and the Role of UNCLOS in the Settlement of the Dispute - Hoogeland, Martijn (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2019)
In the summer of 2016, the Permanent Court of Arbitration (PCA) in the Hague ruled on a territorial dispute between the Philippines and the People’s Republic of China (PRC) over the South China Sea (SCS). In brief, the PCA found the claims of the PRC over most areas of the South China Sea illegitimate and therefore did not recognize the PRC’s claim of territoriality over these waters. In this case note, I explore the details of this PCA case, through a close analysis of the relevant case documents. I conclude the note by looking at different precedents set by this particular case. To do so, I also briefly turn attention to the relevant legal concepts of maritime law and the mechanisms for maritime dispute settlement, provided for in the United Nations Convention on the Law of the Sea (UNCLOS). In doing so, I identify how these legal concepts come into play in this particular case and explore its possible implications on future cases of maritime dispute settlement.